Implikasi Batas Usia Nikah Dalam Undang-Undang No. 16 Tahun 2016 jo Undang-Undang No. 1 Tahun 1974 Terhadap Jumlah Permohonan Dispensasi Nikah di Pengadilan Agama Bekasi - Kurnia Khairunnisa; Suprihatin (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
Initially, the provisions on the age limit for marriage werw present qualitatively. However, along with times and science, quantitative marriage age limits werw born, such as the issuance of law No 16 of 2019 in conjuction with law No. 1 of 1974 concerning Marriage which regulate the legal age limit for new marriages for prospective bride, from 16 years old to 19 years old. This research is a legal research in the type of field research (socio legal research) which aim to determine the implicationa of the aplicationa of law No. 16 of 2019 in conjuction with law No. 1 of 1974 concerning Marriage on the number of dispensation application at the Bekasi Religious Court. The Result of This Study stated that the number of application for dispensation after the issuance of law No 16 of 2019 in conjuction with Law No. 1 of 1974 clearly increased compared to before the enactment of Law No. 16 0f 2019. The increase reached 39 % in year 2020 and 24 % in year 2021. In the perspective of Islamic law, the implication the high demand for dispensation due to Law No 16 of 2019 does not contain problems. This situation can be studied through the ushul fiqh approach to the sad adz-dzara’I concepft as a method of closing difficulties. His Phenomenon can also be seen concept of azimah and rukhshoh.